Emergency Room Length of Stay and Mortality in Patients with Peritonitis-Induced Sepsis at RSUD Dr. Soegiri Lamongan: A Retrospective Pilot Study - Eka Ari Puspita; Ghiffari Maulani; Nur Mujaddidah Mochtar; Imam Suyuthi (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2026)
Sepsis is a life-threatening organ dysfunction caused by a dysregulated host response to infection, with one of the common sources originating from the abdomen. Sepsis remains one of the leading causes of mortality worldwide. One of the factors contributing to increased mortality in sepsis is delayed management in the emergency department. This study aimed to determine the association between emergency department length of stay and mortality in patients with sepsis due to peritonitis at RSUD Dr. Soegiri Lamongan. This study employed a retrospective observational cohort study. Samples were obtained using a total sampling technique from emergency room medical records of post-laparotomy patients between October 2023 and September 2024. Statistical analysis was performed using Fisher’s exact test due to the small sample size. The statistical analysis of 20 patients showed that 1 patient (7.7%) died among those who stayed in the emergency department for ≤ 6 hours, while no deaths (0.0%) were observed among patients with a length of stay > 6 hours. The p-value was 1.000, indicating no statistically significant association between the variables. In conclusion, no statistically significant association was observed in this small cohort.